Industrial Internship Mentoring Model for Industrial Engineering Education in Public Universities - Diniz de Almeida, Maria Gloria [UNESP]; Silva Marins, Fernando Augusto [UNESP]; Pedro Salgado, Andreia Maria [UNESP]; Silveira Marconcini Bittar, Rita de Cassia da; Medeiros de Barros, Jose Glenio; Araujo Junior, Antonio Henriques de; Souza Sampaio, Nilo Antonio de; Fonseca, Bernardo Bastos da; Diniz Baronto, Gessica Naira; Soares Cortes, Andresa Deoclidia (Tempus Publications, 2020)
This article aims to present an industrial internship mentoring model for undergraduate industrial engineering education in public universities. The study proposed that the constructs of mentoring and industrial engineering education can be combined in order to develop a model for teaching. Its reliability has been confirmed by Cronbach's a coefficient test, whereas the statistical hypothesis test has confirmed the validity of the model according to the opinion of 52 pairs of mentors and mentees participating in this applied research with a qualitative methodological approach using a combination of case study and survey. Regarding results, 85% of mentees stated that the model had made a significant positive difference during their internship period, while mentors confirmed that 98% of mentees developed industrial engineering skills and abilities. Thus, the model relies on a detailed procedure about the content that should be assessed in each phase. Its major contribution lies in its pioneering role in developing an industrial internship mentoring model for industrial engineering education and in bringing universities and industries closer together during internship periods.
Keywords: mentoring program; industrial engineering teaching; internship; professional education